Efektifitas Program Gentle Separation dalam Upaya Reduksi Separation Anxiety Anak Usia Dini pada Minggu Awal Sekolah - Badi'atul Husna; Ika Andrini Farida (Universitas Muhammadiyah Metro, 2025)
Separation anxiety is one of the most common emotional challenges experienced by young children during the early stages of school transition. Difficulties in separating from parents may hinder children’s emotional adjustment, participation in classroom activities, and overall readiness for school. This study aimed to examine the effectiveness of the Gentle Separation program in reducing separation anxiety among early childhood students during the initial weeks of school. The program emphasizes gradual desensitization and structured parental involvement, distinguishing it from conventional adaptation approaches that often rely on immediate separation. An experimental research method with a pre-test–post-test design was employed to evaluate the effectiveness of the intervention. Anxiety levels among children in the intervention group were measured before and after the implementation of the program. Data analysis revealed a statistically significant reduction in separation anxiety scores, indicated by a significance value of p < 0.05 and a large effect size. These findings demonstrate that the Gentle Separation program effectively supports children’s emotional readiness by facilitating a safer and more adaptive transition into the school environment. The gradual separation process enabled children to develop a stronger sense of security and emotional comfort during school adjustment. This study highlights the importance of child-centered and humane transition strategies in early childhood education settings. Practically, the findings suggest that the Gentle Separation program may serve as an effective orientation model and can be adopted as a standard transition procedure in early childhood education institutions to support children’s psychological well-being and school readiness.